La incorrecta terminología de los órganos desconcentrados de la oficina nacional de gobierno interior sobre las autoridades políticas - Echevarria Villajulca, Jennifer Raquel (2023)
As a summary, this research work will focus precisely on the terminology used by the Bodies of the National Office of Interior Government, the way in which they refer to political authorities is considered inadequate, since the name of authorities policies goes to those who are democratically elected as a popular election. Those who provide this bad terminology towards these authorities are not elected by popular election either, but occupy a certain position by position of trust. It should be noted that the only public entity in charge of appointing the head of the National Office of the Interior Government is the Ministry of the Interior,so it is worth mentioning that MININTER itself is in charge of esignating the political authorities.